THE IMPACT OF ORGANIZATIONAL AND INSTITUTIONAL COMMUNICATION ON EMPLOYEE PERFORMANCE - ANCA JARMILA GUŢĂ (Annals of the University of Petrosani: Economics)
The paper highlights how communication is, along with motivation and professional competence, the key to efficiency in an organization. All members of an organization spend most of their time communicating in one form or another, regardless of their position in the hierarchy. Since today the number of employees in services and offices exceeds that of the workers in production, there is a greater need to improve communication because greater collaboration between colleagues and hierarchical levels is needed, and teamwork has been generalized that cannot be effective without good collaboration between all team members. Moreover, changes in technology have led to transformations in the structure and activity of organizations and, in particular, public institutions. This is why communication practices and technologies have become increasingly important for all types of organizations. In addition, the role of the manager in the organizational communication process is increased, he is the one who processes the internal and external information, and on the other hand the manager communicates this information to subordinates (he is in the position of disseminator) and to those outside the organization (he is a spokesman).